Test flakiness’ causes, detection, impact and responses: A multivocal review - Tahir A; Rasheed S; Dietrich J; Hashemi N; Zhang L (Elsevier Inc, 2023)
Flaky tests (tests with non-deterministic outcomes) pose a major challenge for software testing. They are known to cause significant issues, such as reducing the effectiveness and efficiency of testing and delaying software releases. In recent years, there has been an increased interest in flaky tests, with research focusing on different aspects of flakiness, such as identifying causes, detection methods and mitigation strategies. Test flakiness has also become a key discussion point for practitioners (in blog posts, technical magazines, etc.) as the impact of flaky tests is felt across the industry. This paper presents a multivocal review that investigates how flaky tests, as a topic, have been addressed in both research and practice. Out of 560 articles we reviewed, we identified and analysed a total of 200 articles that are focused on flaky tests (composed of 109 academic and 91 grey literature articles/posts) and structured the body of relevant research and knowledge using four different dimensions: causes, detection, impact and responses. For each of those dimensions, we provide categorization and classify existing research, discussions, methods and tools With this, we provide a comprehensive and current snapshot of existing thinking on test flakiness, covering both academic views and industrial practices, and identify limitations and opportunities for future research.
Keywords: Flaky tests; Non-deterministic tests; Test bugs; Software testing; Multivocal review